Safety of dapagliflozin in a broad population of patients with type 2 diabetes: Analyses from the DECLARE‐TIMI 58 study. Issue 8 (27th April 2020) - Cahn, Avivit; Raz, Itamar; Bonaca, Marc; Mosenzon, Ofri; Murphy, Sabina A.; Yanuv, Ilan; Rozenberg, Aliza; Wilding, John P. H.; Bhatt, Deepak L.; McGuire, Darren K.; Gause‐Nilsson, Ingrid A. M.; Fredriksson, Martin; et al.
Abstract: Aims: To evaluate comprehensively the safety of dapagliflozin in patients with type 2 diabetes (T2DM), with emphasis placed on potential safety concerns related to the sodium‐glucose co‐transporter‐2 inhibitor class. Methods: In the Dapagliflozin Effect on Cardiovascular Events – Thrombolysis in Myocardial Infarction 58 (DECLARE‐TIMI 58) study, 17 160 patients with T2DM were randomized to dapagliflozin or placebo and followed for a median of 4.2 years. Safety was evaluated in 17 143 patients receiving at least one dose of study drug. Results: Acute kidney injury occurred less frequently with dapagliflozin, and adverse events suggestive of volume depletion were balanced between treatment groups, both irrespective of baseline estimated glomerular filtration rate, blood pressure, diuretic or loop diuretic use (interaction P values >0.05). Fractures and malignancies were balanced between the groups, irrespective of sex, diabetes duration or smoking (interaction P values >0.05) and fewer cases of bladder cancer occurred in the dapagliflozin versus the placebo group. Diabetic ketoacidosis was very rare, but more frequent with dapagliflozin versus placebo (27 vs. 12 patients with events; P = 0.02), yet signs, symptoms and contributing factors were similar in the two groups. Major hypoglycaemia occurred less frequently with dapagliflozin versus placebo, regardless of baseline use of either insulin or sulphonylureas (interaction P values >0.05). There were more adverse events of genital infections leading to discontinuation of study drug in the dapagliflozin versus the placebo group, but serious genital infections were few and balanced between treatment groups. Urinary tract infections, acute pyelonephritis and urosepsis were also balanced between treatment groups. Conclusions: Dapagliflozin was well tolerated. The long duration and large number of patient‐years in DECLARE‐TIMI 58 comprehensively addressed previous safety questions, confirming the robust safety profile of dapagliflozin.